Dimensions of relationship on the background of migration. The case of moldovan adolescents rooted in Italy - ROSCA Tatiana (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Sentimental relationships, according to migration studies, are considered to be the calling card for the integration of immigrants through their children, who, being socialized through the cultural model of the host country, would have more possibilities and predispositions towards relations with the natives, accelerating, in this way, the process of ethnic openness and acceptance of immigrants by the host society. The present work reflects the sentimental tendencies of Moldovan immigrant adolescents from Italy, which derive from parental influences and cultural affiliation. Furthermore, it highlights the dynamics of hypothetical partners' choices, especially when speaking of relational integration in the context of migration.